Geographic Information Systems based performance assessment: Case study of selected medical libraries in Iran - Eskrootchi, Rogheyeh; Janbozorgi, Mojgan; Kumar, Chetan; Yuvaraj, Mayank; Vaziri, Farideh (Malaysian Journal of Library and Information Science, 2020)
The study aims at determining the capability of Geographic Information Systems (GIS) in mapping library performance indicators. Six categories were identified as the potential library performance indicators in the study: per capita space, per capita seat, per capita staff, collection flow, circulation per capita, and per capita costs of providing printed sources. A comprehensive checklist was designed for data collection. The collected data were analysed utilizing ArcGIS version 10.7. Correlations between the six identified library performance indicators were validated in the study. ArcGIS software has the capability to display performance indicators in the form of clear images to conduct suitable analysis. Displaying performance indicators in the form of graphs and tables without using GIS makes data analysis and presentation difficult and it lacks precision and generalization. Maps incorporating performance indicator analysis using GIS, function as blueprints for displaying information on maps. The study validates the capability of GIS in mapping library performance indicators.